International Legal Sources of Aquatic Bioresources Safety in the Caspian Sea - Alexandr S. Lebedev; Arman A. Ginoyan (Евразийская интеграция: экономика, право, политика, 2019)
The present article analyzes international legal sources of aquatic bioresources safety in the Caspian Sea. Because of intensive development of oil and gas fields in the Caspian Sea, poaching and sea level change there was a need of international legal mechanisms as for the protection of its flora and fauna implementation. More than for 25 years Russia, Iran, Azerbaijan, Kazakhstan and Turkmenistan have worked over these mechanisms. Their activity in this field is complicated by differences in understanding of legal status of the Caspian Sea. But even in such conditions Caspian states have reached understanding concerning key moments of aquatic bioresources in the Caspian Sea.